UJI DAYA TERIMA DAN KANDUNGAN ZAT GIZI ES KRIM DENGAN MODIFIKASI BUNGA ROSELLA(Hibiscus sabdariffa L) - Irma Yulita; Fitri Ardiani; Zulhaida Lubis (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2017)
Rosella is one kind of the diversity in the plant world and potentially be a functional food  because rosella contains gossypetin, anthocyanin and glycoside hibiscin, which is believed to be a diuretic (set of urine) and a choleretic effect (expenditure of bile by the liver). Rosella contain bioaktive compounds, namely antioxidant. The content that acts an antioxidants are vitamin C and flavonoids which consists of a flavonol and pigment anthocyanin. See the many benefits of rosella on the human body, need to be develop a processed food product from rosella where the product can be liked by many people and beneficial to health. One of the alternative result of processed from rosella that can be developed is rosella ice cream. The purpose of this research aims to know the acceptability and nutrient content of ice cream with a modification from rosella. This experiment design  was completely randomized design with of two treatments are addition rosella composition of 10% and 20%. Test acceptability of ice cream with a modification from rosella  made against 30 students people of the Faculty of Public Health University North Sumatera and nutrient analysis was tested in Laboratory of Industrial Research and Standarization Agency Medan and Faculty of Biochemistry Faculty Mathematics and Natural SciencesUniversity North Sumatera. The results of organoleptic test on color, aroma, texture, and flavor ice cream showed the most preferred are ice cream with a modification from rosella composition of 10%. Ice cream with a modified from rosella in two variation that give a real assessment of acceptance tests in terms of colour and flavor. However, it does not provide real assessment of acceptance tests in terms of aroma and texture. The result of nutrional content analysis showed that two treatments had vitamin C contents of 63,008 mg/kg and 70,4 mg/kg, and calcium 498 mg, dan 419 mg. It is suggested to the people be able to make of ice cream with a modification from rosella as an alterrnative food products because they contains vitamin C and calcium the body needsand need for sosialization to improve the peoples interest in cultivating rosella plant. Keywords : Rosella, Ice Cream, Acceptability test, Nutrient content